Endovascular Treatment Combined With Standard Medical Treatment Improves Outcomes of Posterior Circulation Stroke: A Systematic Review and Meta-Analysis - Dong, Shuju; Li, Yanbo; Guo, Jian; Luo, Yaxi; Fang, Jinghuan; Tang, Li; He, Li (Frontiers in Neurology, 2022)
Aims: Whether endovascular treatment (EVT) can further improve the prognosis of patients with posterior circulation ischaemic stroke (PCIS) is unclear. This meta-analysis aims to compare the efficacy and safety of PCIS patients treated with EVT plus standard medical treatment (SMT) and SMT alone. Methods: We systematically searched for relevant randomised controlled trials (RCTs) and prospective cohort trials in MEDLINE, EMBASE, and the Cochrane Library up to February 2022. The primary outcome was favourable functional outcome of the modified Rankin Scale (mRS) with scores of 0-2 or 0-3; secondary outcomes included successful recanalization rate, intracranial haemorrhage (ICH) or symptomatic intracranial haemorrhage (sICH) after treatment and 90-day mortality. Results: We identified six studies including 1,385 PCIS patients (957 with EVT plus SMT; 428 with SMT alone). EVT plus SMT substantially improved 90-day functional outcomes compared with SMT alone (mRS score of 0-2: RR=1.95, 95% CI [1.52–2.51], P<0.001; mRS score of 0-3: RR=1.85, 95% CI [1.49–2.30], P<0.001, respectively). Moreover, compared with SMT, combined treatment significantly improved the rate of successful recanalization (RR=5.03, 95% CI [3.96-6.40], P<0.001) and reduced 90-day mortality (RR=0.71, 95% CI [0.63-0.79], P<0.001) despite a higher risk of ICH (RR=6.13, 95% CI [2.50-15.02], P<0.001) and sICH (RR=10.47, 95% CI [2.79-39.32], P=0.001). Conclusion: Low to moderate evidence from RCTs and non-RCTs showed that increased ICH and sICH risk of EVT plus SMT did not translate to higher risk of unfavourable outcomes compared with SMT and could even promote independence at 90 days in a real-world cohort.